Growth modelling of Mexican Creole, Rhode Island Red and Hy-Line Brown birds - Osio-Orihuela, Leonardo; Zárate-Contreras, Diego; Cigarroa-Vázquez, Francisco Antonio; Vazquez-Mendoza, Paulina; González-Cerón, Fernando (Ecosistemas y Recursos Agropecuarios, 2022)
The objective was to characterize the growth of Mexican Creole (MXC), Hy-Line Brown (HLB) and Rhode Island Red (RIR)] birds through non-linearmodels: Gompertz-Laird (NLMGL), Logistic (NLML), Richards (NLMR) and Von Bertalanffy (NLMVB). Seventy birds of each genotype were used. Each bird was identified to record its weight from 7 to 210 d of age. Parameters of each model were estimated through NLIN procedure (Marquardt´s algorithm) of SAS. The next goodness-of-fit criteria were calculated: adjusted determination coefficient, Akaike information criterion and Bayesian information criterion. Growth initial rate (d−1) waslower in MXC birds (0.047 15) than in RIR (0.071 69) or HLB (0.052 16) chickens. Rate of decay was lower in MXC birds with all the four models. Likewise, age of maximum growth (d) of MXC, RIR and HLB birds ranged from 49.4 to 87.9, 60.7 to 81.6, and from 58.7 to 87.8, respectively. On the other hand, the asymptotic weight (g) ranged from 2 068.5 to 2 644.3, 1 902.4 to 2 250.9, and from 2 096.3 to 2 464.5 in MXC, RIR and HLB birds, respectively. The best adjustment of RIR and HLB data was obtained with NLMVB, in contrast, NLMR was a better model for MXC birds, followed by NLMVB. The NLMVB would be the most suitable model for the simultaneous analysis of growth of MXC, RIR and HLB birds.
Keywords: Growth curve; nonlinear models; Creole birds; Rhode Island Red; Hy-Line Brown.